Consumer revolving credit and debt over the life cycle and business cycle - Scott L. Fulford; Scott Schuh (Federal Reserve Bank of Boston, 2015)
Little work has examined how unsecured consumer credit, such as the limit on credit cards, varies over the life cycle, and how consumers respond to changes in their ability to borrow over the short and long term. Using a large panel of credit accounts in the United States, we document that large movements in credit from 1999 to 2015 were accompanied by similar movements in debt, so utilization was nearly constant. Life-cycle variation in consumer credit is similarly large. Credit limits increase rapidly early in life, growing by more than 400 percent between the ages of 20 and 30. Debt grows almost as fast, however, so credit utilization falls slowly throughout the life cycle, reaching 20 percent only by age 70. Individual credit utilization is extremely stable despite the large life-cycle, business cycle, and individual volatility of credit. Stable utilization means that consumer debt is very sensitive to changes in credit limits. Distinguishing between consumers who revolve debt and those who use credit cards only for payments, we find that for revolvers nearly 100 percent of an increase in credit limits eventually becomes an increase in debt.
Keywords: D14; D91; E21; 330